جهود الشيخ الحاج محمد الأمين الكانمي البرنوي في تطوير الخط العربي في السودان الغربي - الدكتور زكريا محمد عبدالله (Universitas Negeri Malang, 2022)
This modest brief research is about: The efforts of Sheikh Al-Hajj Muhammad Al-Amin Al-Kanimi Al-Barnawi in developing Arabic calligraphy in Western Sudan. The researcher chose this topic for many purposes, including: (1) The desire to raise the status of the Arabic language. (2) To highlight the effective attempt that Sheikh Muhammad Al-Amin Al-Kanimi was able to make in the field of Arabic calligraphy. (3) The researcher's longing to study Nigeria's Arabic productions. (4) Encouragement to try to trace the traces of that sheikh. As for the purposes of the research, there are: (1) Expanding the knowledge and intellectual level in the field of Nigerian Arabic calligraphy. (2) Shedding light on Sheikh Muhammad Al-Amin Al-Kanmi’s interest in the Arabic language in Nigeria in particular, and in West Africa in general. Then the research will follow the descriptive approach so as to follow the efforts of Al-Kanmi and express it in a quantitative and qualitative manner, to clarify the characteristics features, and to analyze the data and reach conclusions. The research obtained the following results: (1) Sheikh Muhammad Al-Amin Al-Kanmi was born in the year: one thousand seven hundred and seventy six (1776 AD), and he grew up in a house of knowledge, under the care of his father. Al-Kanimi learned the knowledge of Qur’an from his father (Muhammad Lenga), and the principles of Arabic and Islamic education, then continued to travel to different cities, including: Jerusalem, Mecca, Medina, Fez, Egypt, Tripoli, Qairawan, Tlemcen, and others. He learned the Islamic knowledge and language from its distinguished scholars so that he could navigate many types of knowledge and arts. (2) Al-Hajj Muhammad Al-Amin Al-Kanmi is one of the prominent figures of Arabic calligraphy who made a great contribution to the revitalization and development of Arabic calligraphy in the country of Nigeria, where he was able to impose many poems for various puposes, as well as editing vauablelettershe sent to the leader of Sokoto jihad (Sheikh Othman bin Muhammad Fodio), and the correspondences that he was able to carry out between him and the neighboring countries, and those between him and the King of England.